MODERN METHODS OF SURGICAL TREATMENT OF PATIENTS WITH CHRONIC VENOUS INSUFFICIENCY OF THE LOWER EXTREMITIES - Sunnatov, R.D.; Irnazarov, A.A.; Tajiyev, S.Z. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Open surgical methods or endovascular techniques are usually chosen as an optimal treatment option for the surgical treatment of varicose veins of lower extremities. Open interventions inlvolve general anesthesia and another disadvantage is a cosmetic defect after surgery due to the skin incision performed for access. According to results of the studies, radiofrequency ablation, endovenous laser coagulation and echo-sclerotherapy “foam-form” are the preferred methods, which have several advantages compared to traditional surgical methods that allow the treatment to be performed on an outpatient basis, while preserving the patient’s working capacity and significant cosmetic effect. The advantages and disadvantages of the treatment methods mentioned above, as well as the possibility of their use individually or in combination are still under consideration